Evading strength-ductility trade-off in a metastability engineered layered metallic composite - Roopam Jain; Ravi Sankar Haridas; Prithvi Awasthi; Abhijeet Dhal; Rajiv S. Mishra (Materials & Design)
This investigation demonstrates a unique layered metallic composite (LMC) design strategy which exploits the metastability tunability of the transformative complex concentrate alloys (CCAs). Metastability engineered LMC (ME-LMC) was prepared by sandwiching a relatively less metastable Fe38.5Mn20Co20Cr15Si5Cu1.5 CCA (SFE = 12 mJ/m2) between the two layers of the highly metastable Fe40Mn20Co20Cr15Si5 CCA (SFE = 6 mJ/m2). In ME-LMC, plastic instability of highly metastable alloy got delayed resulting in slight increase in the ultimate tensile strength (UTS) while maintaining comparable ductility compared to the monolithic CCAs. Superior properties of the ME-LMC are attributed to the enhanced activation of transformation and twin systems in the HCP phase due to the generation of biaxial state of stresses originating from the CCA interface affected zones. Enhanced transformation and twinning led to the greater dynamic refinement of the microstructure providing higher strain hardening enabling greater ductility while benefitting from the dynamic Hall-Petch strengthening. A dislocation density evolution based modelling framework is developed to elucidate the enhancement in mechanical properties.